Decontamination of Red Pepper Using Cold Atmospheric Pressure Plasma as Alternative Technique - Abdi, Soheila; Hosseini, Ashrafalsadat; Moslehishad, Maryam; Dorranian, Davoud (Applied Food Biotechnology, 2019)
Background and objective: Non-thermal methods are suggested for decontamination of spices to preserve safety and quality of the products. In this study, effects of atmospheric pressure floating-electrode dielectric-barrier discharge plasma were investigated on red pepper powder, compared to gamma irradiation. Material and methods: To achieve the optimum time of treatment for decontamination, Escherichia coli, Bacillus cereus and Aspergillus flavus as microorganisms in red pepper were exposed to atmospheric pressure floating-electrode dielectric-barrier discharge plasma for 10, 20 and 30 min and the structural changes in microorganisms were investigated using scanning electron microscopy and DNA measurement following exposure. The red pepper was exposed to plasma for 20 min (optimum time) and 10 KGy gamma irradiation. Microbial count, color measurement and sensory evaluation of the samples were assessed before and after treatments. Results and conclusion: Results indicated that the density of surviving bacterial strains decreased when time of exposure increased and this decrease was significant after 10 min (P≤0.05). The complete decontamination was carried out within 20 min. The deformation of cells and destruction of cell wall structures were seen in bacteria and mold following exposure. Data revealed that cold floating-electrode dielectric-barrier discharge plasma for 20 min inactivated red pepper microorganisms as well as gamma irradiation. As a conclusion, floating-electrode dielectric-barrier discharge plasma is an appropriate method to decontaminate the red pepper powder (regardless of color change) and can replace traditional methods without changes in the product quality and taste. Conflict of interest: The authors declare no conflict of interest.